2016
DOI: 10.1111/pce.12763
|View full text |Cite
|
Sign up to set email alerts
|

The antagonistic regulation of abscisic acid‐inhibited root growth by brassinosteroids is partially mediated via direct suppression of ABSCISIC ACID INSENSITIVE 5 expression by BRASSINAZOLE RESISTANT 1

Abstract: Brassinosteroids (BRs) and abscisic acid (ABA) are plant hormones that antagonistically regulate many aspects of plant growth and development; however, the mechanisms that regulate the crosstalk of these two hormones are still not well understood. BRs regulate plant growth and development by activating BRASSINAZOLE RESISTANT 1 (BZR1) family transcription factors. Here we show that the crosstalk between BRs and ABA signalling is partially mediated by BZR1 regulated gene expression. bzr1-1D is a dominant mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 36 publications
4
54
2
Order By: Relevance
“…Because ABA production is induced during drought stress to promote stress tolerance (Cutler et al, 2010), these observations point toward a close relationship between BR and ABA pathways (Zhang et al, 2009b). Indeed, the molecular basis for BR-ABA antagonism has been extensively defined, ranging from interactions between downstream TFs such as BES1 and ABI3 or ABI5 (Ryu et al, 2014;Yang et al, 2016) to BIN2 kinase, a negative regulator of the BR signaling pathway that becomes activated in the presence of ABA (Wang et al, 2018a). BIN2 phosphorylates and promotes the activity of positive regulators in the ABA pathway including SnRK2 kinases (Cai et al, 2014) and TFs such as ABI5 (Hu and Yu, 2014).…”
Section: Br and Aba Pathways Antagonize One Anothermentioning
confidence: 99%
“…Because ABA production is induced during drought stress to promote stress tolerance (Cutler et al, 2010), these observations point toward a close relationship between BR and ABA pathways (Zhang et al, 2009b). Indeed, the molecular basis for BR-ABA antagonism has been extensively defined, ranging from interactions between downstream TFs such as BES1 and ABI3 or ABI5 (Ryu et al, 2014;Yang et al, 2016) to BIN2 kinase, a negative regulator of the BR signaling pathway that becomes activated in the presence of ABA (Wang et al, 2018a). BIN2 phosphorylates and promotes the activity of positive regulators in the ABA pathway including SnRK2 kinases (Cai et al, 2014) and TFs such as ABI5 (Hu and Yu, 2014).…”
Section: Br and Aba Pathways Antagonize One Anothermentioning
confidence: 99%
“…Yang et al (2016) showed that bzr1-1D , a dominant mutant with enhanced BR signaling, was less sensitive to ABA-inhibited primary root growth. ABA INSENSITIVE5 (ABI5) was found to be repressed not only by exogenously applied BR but also by BZR1 itself.…”
Section: Abi5 As the Integrator Of Aba And Other Phytohormone Signalimentioning
confidence: 99%
“…BRASSINOSTEROID INSENSITIVE2 (BIN2), a GSK3-like kinase in the brassinosteroid (BR) signaling pathway, was shown to phosphorylate and stabilize ABI5 during seed germination. By contrast, the BRASSINAZOLE RESISTANT 1 (BZR1) transcription factor could suppress ABI5 expression during root growth (Hu & Yu, 2014;Yang et al, 2016). Interestingly, BRINSENSITIVE1 (BRI1)-EMS-SUPPRESSOR1 (BES1), another key transcription factor in the BR signaling pathway, but not BZR1, is a major contributor to BR-mediated suppression of ABA signaling during seed germination (Ryu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%